Propostas para o Buen Vivir:: a luta mapuche pela construção de um Estado plurinacional no Chile (Revista de História Regional, 2022)
AbstractThe Chilean historical experience is characterized by conflicting relationships between the Mapuche and state power. Araucania, a region located in the south of Chile, was the target of expansionist movements and modernizing projects, that intended to incorporate it into the sphere of public power, civilizing its inhabitants or extinguishing them if necessary. However, the Mapuche have made Araucania and their very existence as an ethnic group part of a long history of struggle against colonialism, racism, identity repression and the illegal occupation of ancestral territories. The objective of this article is to analyze their participation in the Constitutional Convention, considering this political institution as the space of indigenous resistance and of elaboration of proposals for the construction of a new country, plurinational and intercultural. Keywords: Mapuche; Constitutional Convention; plurinationality